2019
DOI: 10.1097/gme.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score of postmenopausal women is positively correlated with bone mineral density and negatively correlated with age and body mass index

Abstract: Objective: Trabecular bone score (TBS), an indirect evaluation of skeletal microarchitecture, is calculated from dual-energy X-ray absorptiometry (DXA). This study aimed to determine the mean TBS values in healthy postmenopausal women and overall association between TBS and demographic features, bone mineral density (BMD) of the lumbar spine and femoral neck, and BMD to body mass index (BMI) ratio of the lumbar spine. Methods: Fifty-three postmenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
6
11
0
1
Order By: Relevance
“…Previous investigations have shown that HRT and increased BMI prevent bone loss. ( 10,11,29‐32 ) Our study found similar results. The use of HRT appears to be associated with lower postmenopausal bone loss and the women in the lowest bone loss quartile had the greatest increase in BMI.…”
Section: Discussionsupporting
confidence: 85%
“…Previous investigations have shown that HRT and increased BMI prevent bone loss. ( 10,11,29‐32 ) Our study found similar results. The use of HRT appears to be associated with lower postmenopausal bone loss and the women in the lowest bone loss quartile had the greatest increase in BMI.…”
Section: Discussionsupporting
confidence: 85%
“…Another issue that should be taken into account when assessing bone microarchitecture in patients treated with GCs is the negative correlation of TBS with BMI. A similar correlation was reported in the small study by Torgutalp et al [20], suggesting that abnormalities of the bone tissue microarchitecture may be present more frequently in patients with higher BMI. Still, BMI was not associated with increased fracture occurrence in our study.…”
Section: Effect Of Glucocorticoids On Bone Microarchitecturesupporting
confidence: 87%
“…Increasing age was a predictor of increased risk of fracture, which has been confirmed in previous studies. [35][36][37] The duration of illness in postmenopausal women was one of the predictors of a higher risk of fracture.…”
Section: Discussionmentioning
confidence: 99%